Socio-economic development of mining communities : a juridical and comparative study of responsibilities and liabilities of mining companies in South Africa - Mokgokong, Mokgadi Margaret (My University, 2024)
In South Africa, the right to a clean environment and environmental sustainability is constitutionally guaranteed. Also, the Mineral and Petroleum Resources Development Act (MPRDA) sets certain obligations to mining and the extractive industry in general, including having to conduct their operations in a manner that takes into account the socio-economic conditions of the mining communities. However, preliminary investigations suggest that these obligations are being ignored and the rights of mining communities are violated daily by the mining industry. Mining communities often bear the brunt of the negative effects of mining operations. With the economic expansion trend in Africa and multinational corporations (MNCs) conducting extractive operations, the protection of mining communities remains a critical issue for the extractive industry. Mining communities must be part of the mining stakeholders who should benefit from the equitable and sustainable distribution of mineral resources. The starting point is to have in place sustainable mining practices that extend to the promotion of the socioeconomic development of mining communities or communities affected by mining activities. The study moves from the proposition that there is a need to develop a corporate social responsibility (CSR) theory or approach that addresses the specific circumstances of rural mining communities. This study further contents that the enshrinement of environmental rights in the South African Constitution not only requires mining communities to be aware of their environmental rights and the rights to sustainable development. Failure to understand the importance of these rights and the relationship between these rights will ensure that sustainable development will remain paper tigers. The methodology used in the research is primarily desktop which entails the study of primary and secondary literature. The adopted descriptive, doctrinal analysis and comparative perspectives research methods. Using CSR as the main theoretical underpinning of the study, the researcher conducts a juridical and comparative investigation of the contribution of mining companies in South Africa towards the socio-economic development of rural mining communities. Theories of sustainable development and the human rights-based approach will be complementary conceptual frameworks towards the execution of the study. The study concludes that there is a plethora of legislation that regulates other aspects of CSR, but very few that focus on socioeconomic development and the protection of the rights of dwellers of mining communities. To this end, one of the recommendations by the researcher is the introduction of legislation that regulates the socio-economic development of mining communities through CSR. The researcher provides a draft recommended legislation.
Thesis (LLD.) -- University of Limpopo, 2024
Keywords: Accountability; Companies; Corporate Social Responsibility; Liabilities; Mining Communities; Socioeconomic Development; Sustainable Development; Social responsibility of business; Liability (Law); Mineral industries; Sustainable development -- South Africa